Pertanggungjawaban Hukum Pelaku Usaha Industri Rumah Tangga Pangan dan Mekanisme Pengawasan Pemerintah terhadap Pelabelan dan Promosi Produk Pangan Secara Daring - Asy Syifa Anroneka, Ibnu; Octora, Rahel (CV Rewang Rencang, 2026)
The utilization of social media and marketplaces by Home Industry Food (Industri Rumah Tangga Pangan – IRTP) entrepreneurs increases the risk of labeling and promotion that does not comply with legal provisions. This research analyzes the legal liability of IRTP entrepreneurs and government oversight regarding the labeling and promotion of food products online through a normative juridical method. The results indicate the existence of civil, criminal, and administrative liabilities. Meanwhile, government oversight has not been effectively integrated; thus, strengthening cross-institutional coordination is required to address these challenges.